HUBUNGAN FAKTOR RISIKO DERMATITIS PADA PETANI : (STUDI LITERATUR) - Nanda Nanda; Susilawati Susilawati (CV. ADIBA ADISHA AMIRA, 2023)
Dermatitis occurs in informal workers who generally pay little attention to sanitation and protection of their own health, for example farmers. This study aims to determine the risk factors for dermatitis in farmers in Muara Sindang Village, the Working Area of ​​the UPTD Kisam Ilir Health Center, OKU Selatan Regency in 2020. This research is a study in the form of a Literature Review. Results of the literature review The findings in the article show that there is a significant relationship between the use of personal protective equipment and the incidence of dermatitis in farmers with a p value of 0.013, there is a significant relationship between personal hygiene and the incidence of dermatitis in farmers with a p value of 0.000, and there is a significant relationship between working time with the incidence of dermatitis in farmers. There is a significant relationship between the use of personal protective equipment, personal hygiene and working time with the incidence of dermatitis